Should we put locals in charge? Managing relationships within prospective us – South African joint ventures - Akande, Will Adebowale; Adetoun, Bolanle Eliz; Tserere, Magdeline Makgauta; Adewuyi, Modupe Fal; Akande, Esther Titilola (Journal of Business Economics and Management, 2010)
Using a data set derived from South African managers in our empirical analysis of potential U.S.‐South Africa agreements. The picture that emerges from the analysis, posits that the need for highest work performance, knowledge management and strict control is high and the South African government's administrative barriers seem to be the most crucial problems for the prospective joint ventures. Furthermore, South African managers endorse issues such as plan for knowledge acquisition, distribution, interpretation and organizational memory/performance. US companies invest in South Africa to gain access to its market and South African companies get into joint ventures with US companies to tap into the appropriate knowledge know‐how and financial resources. Key directions for future research in international business stemming from the conceptual framework are also highlighted.Ar vietiniai gyventojai gali užimti vadovaujančias pareigas? Valdymo santykiai galimose bendrose JAV ir Pietų Afrikos įmonėseSantrauka. Galimų JAV ir Pietų Afrikos sutarčių empirinei analizei buvo naudoti duomenys, surinkti iš Pietų Afrikos įmonių vadovų. Gauti analizės rezultatai parodė, kad didesnio darbo našumo, žinių valdymo ir griežtos kontrolės poreikis yra didelis ir kad administraciniai Pietų Afrikos vyriausybės barjerai yra viena iš didžiausių kliūčių bendroms įmonėms kurtis. Pietų Afrikos įmonių vadovai pritaria tokiems klausimams, kaip žinių įgijimo planai, platinimas, interpretavimas ir organizacinė atmintis. JAV įmonės investuoja į Pietų Afriką norėdamos įeiti į jos rinką. Pietų Afrikos įmonės susijungia su JAV įmonėmis, norėdamos gauti reikalingų žinių (know-how) ir finansinių išteklių. Straipsnyje išryškinama pagrindinė tarptautinio verslo ateities tyrimų kryptis.Reikšminiai žodžiai: valdymas, pasitikėjimas, tarptautinės įmonės, JAV ir Pietų Afrikos aljansai.First Published Online: 10 Feb 2011